2007
DOI: 10.1113/expphysiol.2006.033159
|View full text |Cite
|
Sign up to set email alerts
|

Prior sustained hypoxia attenuates interaction between hypoxia and exercise as ventilatory stimuli in humans

Abstract: Both exercise and hypoxia increase pulmonary ventilation. However, the combined effects of the two stimuli are more than additive, such that exercise may be considered to potentiate the acute ventilatory response to hypoxia (AHVR), and vice versa. Exposure to sustained hypoxia of 8 h duration or more has been shown to increase the acute chemoreflex responses to hypoxia and hypercapnia. The purpose of this study was to determine whether sustained exposure to hypoxia also changed the stimulus interaction between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2008
2008
2010
2010

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Indeed, Wood et al (2007) have demonstrated that this interaction is itself affected (reduced) by a period of prior VAH, and conclude that there may be some interrelation between these processes.…”
Section: Discussionmentioning
confidence: 95%
“…Indeed, Wood et al (2007) have demonstrated that this interaction is itself affected (reduced) by a period of prior VAH, and conclude that there may be some interrelation between these processes.…”
Section: Discussionmentioning
confidence: 95%
“…Both exercise and hypoxia increase pulmonary ventilation. However, the combined effects of the two stimuli are more than additive, such that exercise may be considered to potentate the acute ventilatory response to hypoxia [20]. These data contribute to a better understanding of important aspects of alteration of respiratory system reactive features in the process of sustained physical loads which are closely connected with special work capacity manifestation under different environmental conditions.…”
Section: Discussionmentioning
confidence: 98%